Điều khiển các dây chuyền sản xuất linh hoạt - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
In the maner of system theory the manufacturing systems will be seen as a complexity of  technological process with some more of less flexible control strategies. In this paper a complexity of technological process is considered. Some basic configurations and adjustement  possibilities of flexible manufacturing systems are also provid.